2023
DOI: 10.1097/iop.0000000000002264
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Artifacts on MRI

Abstract: Purpose: To describe artifacts on orbital MRI, which led to an incorrect radiology report. Methods: Retrospective chart review of patients identified from the orbital databases at the Royal Adelaide Hospital and University of Wisconsin Hospital. Patients who had artifacts on orbital MRI that led to an incorrect radiology report were included. Records were evaluated for age at imaging, gender, MRI sequence, laterality, and location of artifact, radiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[19] Especially for patients who are inconvenient to admitted to the hospital for examination, the implementation of the "Internet + Nursing" model can be booked through the network, requesting professional nurses to visit the home, so as to access to medical care more conveniently and achieve the purpose of promoting the recovery of the disease. [20] This study compared the recovery of the 2 groups of patients, and the results showed that patients who engaged with our "Internet + Nursing" platform and booked home nursing appointments demonstrated better out-of-hospital visual acuity and ocular surface symptoms, suggesting that "Internet + Nursing" can promote the recovery of patients.…”
Section: Discussionmentioning
confidence: 92%
“…[19] Especially for patients who are inconvenient to admitted to the hospital for examination, the implementation of the "Internet + Nursing" model can be booked through the network, requesting professional nurses to visit the home, so as to access to medical care more conveniently and achieve the purpose of promoting the recovery of the disease. [20] This study compared the recovery of the 2 groups of patients, and the results showed that patients who engaged with our "Internet + Nursing" platform and booked home nursing appointments demonstrated better out-of-hospital visual acuity and ocular surface symptoms, suggesting that "Internet + Nursing" can promote the recovery of patients.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies on MR artifacts affecting the eye have focused mainly on the optic nerve, anterior and posterior chamber, ciliary body, iris, lens, and extraocular muscles but have not examined banding artifacts within the globe [ 6 ]. It has been shown that artifacts in the inferior orbital region can be mistaken for neoplastic or inflammatory orbital diseases, potentially leading to unnecessary orbital biopsies or misdiagnoses [ 7 ]. To analyze if banding artifacts of the eye are potentially homogenous and thus resulting from the magnetic field or are part of biological signals underlying pathophysiological processes in diseases of the eye, the angles of the bands were analyzed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%